See, move, wonder: supporting young children with low science capital to learn from science museum objects - Naomi Haywood (Science Museum Group Journal)
Museum visits by school groups contribute towards life-long science engagement. This is likely to be particularly true for young children who have low science capital. There is only limited research on how museums can support low science capital school groups to engage and learn, particularly in object-rich galleries. The current research addresses this gap. It considers how a simple resource supports playful learning in two object-rich galleries. The resource invites children to find objects and interact with the objects through observation, movement and wondering. Some 92 children (4–7 years) and 15 adults in seven school groups were observed using the resource and then subsequently interviewed. Findings show that encouraging children to search for objects, move in relation to objects and wonder about objects supports learning. Movement and gestures were central to how children experienced the objects as these embodied forms of cognition did not require specific understanding or vocabulary. These findings show that museums can support low science capital young children to learn from objects through a focus on bodily experiences. The theoretical implications of these findings include the value of embodied cognition theory in supporting object engagement and learning, particularly for young children with low science capital.